MORFOMETRIA DA MICROBACIA HIDROGRÁFICA DO CÓRREGO BURACÃO, UBERABA-MG - Ferreira Guidolini, Janaína; Neves Araújo, Marcus Vinícius; Domingues Dias Júnior, Miguel; Cristina Tarlé Pissarra, Teresa; Lúcia Abdala, Vera (Electronic Journal "Fórum Ambiental da Alta Paulista", 2013)
.